Microbial deterioration and degradation of Polymeric materials (Journal of biochemical technology, 2010)
Polymeric materials due to its structural versatility are widely used in aerospace applications, aviation and space industries. As they are potential source of carbon and energy for heterotrophic microorganisms including bacteria and fungi in several ways its biodegradation affect these industries. The information on degradability can provide fundamental information facilitating design and life-time analysis of materials. Literature survey shows that polymers which are susceptible to biofilm formation includes paints, adhesives, plastics, rubbers, sealants, FRPCMs, lubricating materials, fuels etc. Even though the understanding of polymer degradation has been advanced in recent years the subject is still inadequately addressed because of the lack of information available. The review focuses on polymer biodeterioration and biodegradation and its mechanisms, the types of microorganisms involved, the reactions of enzymes of importance in the biodegradation of polymers, consequences, of biodegradation, the factors involved in biodegradation of polymers and its prevention and the tests used to evaluate it.